2020
DOI: 10.1109/access.2020.2986267
|View full text |Cite
|
Sign up to set email alerts
|

Small Sample Classification of Hyperspectral Remote Sensing Images Based on Sequential Joint Deeping Learning Model

Abstract: colleges and universities young talents introduction plan construction team project: big data and business intelligence social service innovation team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…e proposed approach firstly introduces the core architecture, working principle, and related ecosystem of the Hadoop platform and then introduces the basic ideas of the data mining theory of big data analysis and the common algorithms of data mining are outlined. Finally, the principle of convolutional neural network [26][27][28][29][30][31] and the two-branch algorithm proposed in this paper are explained. Figure 2 shows the overall framework of the proposed approach.…”
Section: Methodsmentioning
confidence: 99%
“…e proposed approach firstly introduces the core architecture, working principle, and related ecosystem of the Hadoop platform and then introduces the basic ideas of the data mining theory of big data analysis and the common algorithms of data mining are outlined. Finally, the principle of convolutional neural network [26][27][28][29][30][31] and the two-branch algorithm proposed in this paper are explained. Figure 2 shows the overall framework of the proposed approach.…”
Section: Methodsmentioning
confidence: 99%
“…Krizhevsky et al [31] proposed a large, deep convolutional neural network to classify the 1.2 million high-resolution images in ImageNet, and achieved record-breaking results. Wang et al [32] proposed a sequential joint deep learning algorithm that was found to achieve powerful performance in the prediction of hyperspectral images of small samples.…”
Section: Deep Learningmentioning
confidence: 99%
“…They then construct the relationship between the features through a graph convolution neural network and use the NWPU-RESISC45 data and a private data set to verify the effectiveness of the attention mechanism. Zesong Wang et al [23] constructed a multiattention mechanism model. By combining the original attention feature with the average pooling attention feature and the global average pooling attention feature, more a priori knowledge is obtained, which supports later feature mining.…”
Section: Related Researchmentioning
confidence: 99%